Latin Empire of Constantinople, the Jochids and Crimea in the Mid-Thirteenth Century » - Aleksandar Uzelac (Золотоордынское обозрение, 2015)
The aim of this paper is the analysis of relations between the Latin Empire of Constantinople and Ulus of Jochi (the Golden Horde). It is primarily focused upon the diplomatic mission of Baldwin of Hainaut, which took place approximately between 1249 and 1252. As a representative of the namesake Latin Emperor, Baldwin of Hainaut led negotiations with the Batu’s son Sartak, and then, he traveled to the Far East, where he possibly met with the Great Khan Möngke. The aim of the mission was to secure the Mongol support for the defense of Constantinople against aggressive aspirations of the Empire of Nicaea. The immediate results of the Baldwin’s mission are not known, but it is certain that they led to the establishment of the diplomatic relations between the Latin Empire and the Jochids. It is confirmed by the fact that the famous Flemish traveler William of Rubruck carried recommendations of the Latin emperor to a Tatar representative who governed the lands to the north of Crimea. Exactly these recommendations provided Rubruck safe passage through the Tatar territory. Important factor that led to the Baldwin’s enterprise were activities of Venetian and other Italian merchants. They served as primary intermediaries between the Frankish establishment of Constantinople and the Tatars, but they were not the only ones who played this role. Political and ecclesiastical elite of the Crimean cities, especially of its main port Soldaia, also had important place in these contacts. In the mid-thirteenth century, the Crimea became a contact zone between the two civilizations. In Crimea, western and the Tatar political interests intermingled, as a result of the strategic location of the peninsula, commercial activities of its inhabitants and the cosmopolitan character of the Crimean urban centers.